Mitigating bias blind spot via a serious video game. (September 2016) - Bessarabova, Elena; Piercy, Cameron W.; King, Shawn; Vincent, Cindy; Dunbar, Norah E.; Burgoon, Judee K.; Miller, Claude H.; Jensen, Matthew; Elkins, Aaron; Wilson, David W.; Wilson, Scott N.; Lee, Yu-Hao
Abstract: We employed a serious video game to train participants on bias blind spot (BBS), capturing training effects on BBS mitigation and knowledge at three points in time. Experiment 1 (N = 703) compared the effects of hybrid training (a combination of implicit and explicit training) to implicit training; Experiment 2 (N = 620) tested the effects of just-in-time versus delayed feedback; and Experiment 3 (N = 626) examined the effects of singleplayer versus multiplayer learning environments. We also tested differences in game duration (30 vs. 60 min play) and repetition (single vs. repeated play). Overall, the video game decreased BBS linearly over time and increased BBS knowledge at posttest, but knowledge decayed at 8-week posttest. These and other results are discussed, along with the implications, limitations, and future research directions. Highlights: We developed a serious videogame to train participants on bias blind spot (BBS). In three experiments, playing the game decreased BBS linearly over time. The game also consistently increased BBS knowledge at the first posttest. However, the effects on knowledge decayed at the 8-week posttest. We also found that repeated exposure to the game increased BBS knowledge.